2020
DOI: 10.1037/ser0000339
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of MMPI-2-Restructured Form (MMPI-2-RF) validity scale scores observed across Veteran Affairs settings.

Abstract: The purpose of this investigation is to provide descriptive information on veteran response styles for a variety of VA referral types using the Minnesota Multiphasic Personality Inventory (MMPI)-2-Restructured Form (MMPI-2-RF), which has well-supported protocol validity scales. The sample included 17,640 veterans who were administered the MMPI-2-RF between when it was introduced to the VA system in 2013 until May 31, 2015 at any VA in the United States. This study examines frequencies of protocol invalidity ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…In general, those excluded from analysis most frequently demonstrate patterns of profile invalidity evidenced by elevations on the over-reporting scores as is consistently observed within the VA (see Ingram et al 2019). Generally, valid participants across the four settings were demographically similar (Table 1).…”
Section: Methodsmentioning
confidence: 69%
See 3 more Smart Citations
“…In general, those excluded from analysis most frequently demonstrate patterns of profile invalidity evidenced by elevations on the over-reporting scores as is consistently observed within the VA (see Ingram et al 2019). Generally, valid participants across the four settings were demographically similar (Table 1).…”
Section: Methodsmentioning
confidence: 69%
“…Of note, clinically significant elevations were relatively common across settings, which likely reflects the high rate of complex and comorbid mental health needs of veterans, as well as the centrality of trauma-experiences to their difficulties. To some extent, these elevations may also be due to the frequency of compensation and pension evaluations, which may impact response style in spite of invalid responding detection methods (e.g., Ingram et al 2019;Nelson et al 2011;Ray 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study included only those patients whose assessments were conducted in PTSD Clinical Team (PCT) settings. We excluded patients who scored above the recommended validity cut-scores on the MMPI-2-RF as such scores indicate invalid responding and bias substantive scale elevations (Ingram et al, 2019b). We excluded individuals whose electronic medical records indicated that they did not serve in Vietnam or Gulf War periods.…”
Section: Participantsmentioning
confidence: 99%